(untitled) (Annals of Medical Research, 2023)
Aim: The aim of the present study is to evaluate the results of liver transplantation (LT) in pediatric Wilson disease (WD) with a specific sub-analysis in patients with neuropsychiatric symptoms. Materials and Methods: Demographic, operative, laboratory and neurologic findings of 23 pediatric patients with WD that underwent LT were analyzed by examining the patient charts. Results: Median age of the patients was 13 ( 7 to 17) years. Median Wilson’s Index scores of the patients were 7 (5-13). Median Child-Pugh Score, MELD-Na and PELD scores of the patients were 10 (5-12), 19 (8-34) and 25.4 (8.4-30.7); respectively. Eight patients (34.8%) had Kayser-Fleischer rings on examination. Five patients (21.7%%) presented with acute decompensated Wilson’s disease. Fifteen patients (65.2%) received living donor liver transplantation. Totally, 10 patients (43,4%) had nervous system involvement in the preoperative period. Two patients fully recovered; 2 patients showed partial recovery. On the other hand, 4 patients showed no improvement and 2 patients had progression of their disease in the postoperative period. Conclusions: The results of the present study show that LT is an effective and safe alternative in end-stage liver failure in WD. However, in these patients, nervous system involvement may not improve despite successful LT.